GAMBARAN MARRIED BY ACCIDENT (MBA) PADA REMAJA (STUDI KOMPREHENSIF DITINJAU DARI HUKUM PERDATA, ADAT ISTIADAT SUMBAWA, PSIKOLOGIS DAN EKONOMI): Psikologi Klinis dan sosial, - atmasari, ayuning; Robidah; Rosandi, Fitra Hasri (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Adolescence is a transitional period that leads to an increased attraction to the opposite sex, which may result in promiscuity and unplanned pregnancies, forcing teenagers into marriage. This study aims to describe MBA in adolescents through a comprehensive perspective, including civil law, Sumbawa customary law, psychology, and economics. The research method used is qualitative with a comprehensive approach. The results show that the resolution of MBA issues begins with customary deliberation, followed by formal legal recognition to provide legal protection for the marriage status and the child born. These issues are closely related to psychological subjek, influenced by unstable family backgrounds and a lack of supportive environments. Economic factors also worsen the situation, as financial limitations hinder the ability to build a stable household. These four dimensions interact and shape the conflict resolution dynamics, highlighting the importance of a holistic approach to provide sustainable solutions for adolescent MBAs.